Evaluating Different Virulence Traits of Klebsiella pneumoniae Using Dictyostelium discoideum and Zebrafish Larvae as Host Models - Marcoleta, Andrés E.; Varas, Macarena A.; Ortiz-Severín, Javiera; Vásquez, Leonardo; Berríos-Pastén, Camilo; Sabag, Andrea V.; Chávez, Francisco P.; Allende, Miguel L.; Santiviago, Carlos A.; Monasterio, Octavio; Lagos, Rosalba (Frontiers in Cellular and Infection Microbiology, 2018)
Multiresistant and invasive hypervirulent Klebsiella pneumoniae strains have become one of the most urgent bacterial pathogen threats. Recent analyses revealed a high genomic plasticity of this species, harboring a variety of mobile genetic elements associated with virulent strains, encoding proteins of unknown function whose possible role in pathogenesis have not been addressed. K. pneumoniae virulence has been studied mainly in animal models such as mice and pigs, however, practical, financial, ethical and methodological issues limit the use of mammal hosts. Consequently, the development of simple and cost-effective experimental approaches with alternative host models is needed. In this work we described the use of both, the social amoeba and professional phagocyte Dictyostelium discoideum and the fish Danio rerio (zebrafish) as surrogate host models to study K. pneumoniae virulence. We compared three K. pneumoniae clinical isolates evaluating their resistance to phagocytosis, intracellular survival, lethality, intestinal colonization, and innate immune cells recruitment. Optical transparency of both host models permitted studying the infective process in vivo, following the Klebsiella-host interactions through live-cell imaging. We demonstrated that K. pneumoniae RYC492, but not the multiresistant strains 700603 and BAA-1705, is virulent to both host models and elicits a strong immune response. Moreover, this strain showed a high resistance to phagocytosis by D. discoideum, an increased ability to form biofilms and a more prominent and irregular capsule. Besides, the strain 700603 showed the unique ability to replicate inside amoeba cells. Genomic comparison of the K. pneumoniae strains showed that the RYC492 strain has a higher overall content of virulence factors although no specific genes could be linked to its phagocytosis resistance, nor to the intracellular survival observed for the 700603 strain. Our results indicate that both zebrafish and D. discoideum are advantageous host models to study different traits of K. pneumoniae that are associated with virulence.